2020
DOI: 10.3390/jpm10040209
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Studies of a Rare CF-Causing Mutation in the Second Nucleotide Binding Domain (c.3700A>G) Show Robust Functional Rescue in Primary Nasal Cultures by Novel CFTR Modulators

Abstract: The combination therapies ORKAMBITM and TRIKAFTATM are approved for people who have the F508del mutation on at least one allele. In this study we examine the effects of potentiator and corrector combinations on the rare mutation c.3700A>G. This mutation produces a cryptic splice site that deletes six amino acids in NBD2 (I1234-R1239del). Like F508del it causes protein misprocessing and reduced chloride channel function. We show that a novel cystic fibrosis transmembrane conductance regulator CFTR modulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…This finding highlights that both cellular models can be used to predict the clinical benefit of a single drug or combination of drugs for a certain individual, despite the fact that CFTR function in pHNEs was measured by an Ussing chamber, whereas in intestinal organoids, it was indirectly measured by organoid swelling. Several groups already use either of these two models to predict responses to CFTR modulator drugs [ 16 , 17 , 18 , 20 , 39 , 40 , 46 , 47 , 48 , 49 ], but here, we show that the establishment of a responder or non-responder was the same in both models ( Figure 3 ), using both types of samples from the same individual. The only exception was the individual with the D614G/F508del genotype who was considered a non-responder through pHNE analysis but appeared as a responder from intestinal organoid data.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…This finding highlights that both cellular models can be used to predict the clinical benefit of a single drug or combination of drugs for a certain individual, despite the fact that CFTR function in pHNEs was measured by an Ussing chamber, whereas in intestinal organoids, it was indirectly measured by organoid swelling. Several groups already use either of these two models to predict responses to CFTR modulator drugs [ 16 , 17 , 18 , 20 , 39 , 40 , 46 , 47 , 48 , 49 ], but here, we show that the establishment of a responder or non-responder was the same in both models ( Figure 3 ), using both types of samples from the same individual. The only exception was the individual with the D614G/F508del genotype who was considered a non-responder through pHNE analysis but appeared as a responder from intestinal organoid data.…”
Section: Discussionmentioning
confidence: 57%
“…Our results show a significant and high correlation (95%) between CFTR basal function measured in pHNEs and rectal biopsies ( Figure 2 ). This was somewhat expected since measurements of CFTR-mediated Cl − secretion in both pHNEs and rectal biopsies have already been published by several independent groups and show good correlations with clinical data [ 16 , 20 , 31 , 33 , 40 ]. Additionally, CFTR activation in these two models has some practical similarities since CFTR is activated by the same concentration of Fsk and IBMX (2 µM and 100 µM, respectively) and CFTR activity is measured by the same electrophysiological technique, i.e., in the Ussing chamber.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…On the other hand, the clinical response size is highly variable even in patients homozygous for F508del [ 7 ]. Therefore, we and others are examining the utility of modulator testing on patient-derived nasal cultures or rectal organoids to predict clinical response size [ 18 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to ICM, rectal biopsies can also be used to generate patient-derived intestinal organoids as a versatile model system for preclinical testing of investigational compounds targeting rare CFTR mutations that are not eligible for treatment with an approved CFTR modulator [ 59 , 60 ]. In addition, nasal or bronchial epithelial cells collected by brushings can be expanded and differentiated under air-liquid interface conditions to enable testing of multiple drug candidates in primary airway epithelial cultures derived from individual patients harboring specific CFTR mutations [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Several preclinical studies in these patient-derived model systems showed that the triple combination of elexacaftor–tezacaftor–ivacaftor, as well as several novel modulator combinations improve CFTR function in class II mutations other than F508del , as well as other rare CFTR mutations [ 68 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Potential Use Of Icm For Personalized Medicine For Patients With Rare Mutations and High Unmet Needmentioning
confidence: 99%